2018
DOI: 10.1016/j.drugalcdep.2018.01.030
|View full text |Cite
|
Sign up to set email alerts
|

Factors related to cigarette smoking and intent to quit among adolescent inpatients with psychiatric and substance use disorders

Abstract: Smoking was related to several psychiatric and substance use problems. Notably, adolescent psychiatric inpatient smokers reported intention to quit smoking regardless of psychiatric disorders, psychiatric symptom severity, or other substance use.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 24 publications
0
4
0
1
Order By: Relevance
“…Richter et al (2009) further showed that risky behaviors of children and adolescents are rarely affected by income and social status of parents [35]. Considering the fact that various studies point to the role of individual and environmental factors in high-risk behaviors [36][37][38] and also the lack of conclusive ndings regarding the role of parents' occupation in alcohol and substance abuse in adolescence, it is concluded that parents' occupation as a predictor of substance use disorder in adolescence has a contextual nature. In other words, the way parents' occupation is related to substance use disorder in children and adolescence could vary in different communities.…”
Section: Discussionmentioning
confidence: 99%
“…Richter et al (2009) further showed that risky behaviors of children and adolescents are rarely affected by income and social status of parents [35]. Considering the fact that various studies point to the role of individual and environmental factors in high-risk behaviors [36][37][38] and also the lack of conclusive ndings regarding the role of parents' occupation in alcohol and substance abuse in adolescence, it is concluded that parents' occupation as a predictor of substance use disorder in adolescence has a contextual nature. In other words, the way parents' occupation is related to substance use disorder in children and adolescence could vary in different communities.…”
Section: Discussionmentioning
confidence: 99%
“…While several studies have evaluated screening in emergency departments and psychiatric wards [13,14,15,16,17,18], very little is known about effective tobacco use screening for inpatient adolescents. One study in Australia found that patients admitted to an adolescent medical unit had the highest proportion of any psychosocial screening completed at 80%, but this did not focus exclusively on tobacco use screening [13].…”
Section: Discussionmentioning
confidence: 99%
“…Während gelegentlich die Zweckmäßigkeit von Tabakkontrolle und Tabakentwöhnung im Rahmen psychiatrischer Behandlungen angezweifelt wurde [17], ist mit wachsender Evidenz festzustellen, dass die Tabakentwöhnung eher positive Effekte auf Verlauf und Progno- se psychischer Störungen aufweist [16]. Tatsächlich möchte etwa jede zweite rauchende Person in der KJP aufhören [18]. Bei KJP-Patientinnen und Patienten ist Abstinenz ein ebenso realistisches Ziel (8,5-28,1 % nach 1-12 Monaten [19,20]) wie bei nichtpsychiatrischen Jugendlichen (5,6 %-21,8 % nach 6 Monaten [21,22]).…”
Section: Nutzen Der Entwöhnungunclassified